2018
DOI: 10.1186/s13229-018-0223-7
|View full text |Cite
|
Sign up to set email alerts
|

Symptom severity in autism spectrum disorder is related to the frequency and severity of nausea and vomiting during pregnancy: a retrospective case-control study

Abstract: BackgroundNausea and vomiting during pregnancy (NVP) is thought to be caused by changes in maternal hormones during pregnancy. Differences in hormone exposure during prenatal life have been implicated in the causal pathways for some cases of autism spectrum disorder (ASD). However, no study has investigated whether the presence and severity of NVP may be related to symptom severity in offspring with ASD.MethodsA large sample of children with ASD (227 males and 60 females, aged 2 to 18 years) received a clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…Previous studies on the association of exposure to severe prolonged NVP and the risk of adverse health outcomes in the offspring are scarce. Two are mentioned in the introduction [ 10 , 11 ], and these much smaller studies ( n = 560 and 287, respectively) reported some changes in cognition and emotional and behavioral problems. The present study was much more powerful than previous studies, with a very large sample ( n = 10,710) demonstrating that a wide range of psychiatric (Table S2) and cognitive measures (Table S2) are associated with severe prolonged NVP and with external-validation of the major psychiatric findings in an independent national sample ( n = 2,092,897, Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on the association of exposure to severe prolonged NVP and the risk of adverse health outcomes in the offspring are scarce. Two are mentioned in the introduction [ 10 , 11 ], and these much smaller studies ( n = 560 and 287, respectively) reported some changes in cognition and emotional and behavioral problems. The present study was much more powerful than previous studies, with a very large sample ( n = 10,710) demonstrating that a wide range of psychiatric (Table S2) and cognitive measures (Table S2) are associated with severe prolonged NVP and with external-validation of the major psychiatric findings in an independent national sample ( n = 2,092,897, Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…These conditions play a crucial role in shaping fetal development and subsequent child brain and behavior development [ 6 9 ]. One study reported that severe prolonged NVP was associated with increased internalizing and externalizing behaviors in the offspring which reflect mood changes and conflict with others [ 10 ] and another reported decreased social responsiveness [ 11 ], highlighting the need for a large-scale evaluation of the long-term effects of exposure to severe prolonged NVP. As observed in two recent studies, clinical diagnosis of maternal hyperemesis gravidarum was associated with an increased risk of autism spectrum disorders in the offspring [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…One such factor is increased maternal weight which has been linked to higher levels of prenatal testosterone 35 and to autistic traits 36 . Future research could also consider the potential etiological influence of nausea and vomiting during pregnancy which has been found to be related to increased symptom severity in ASD 37 . Maternal nausea and vomiting during pregnancy is thought to involve the dysregulation of several hormones including estrogens 38 which may have feminising properties.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of clinically diagnosed autism, both very low and very high levels of hCG have been found in maternal serum, leading to a "U-shaped" association when studying both males and females (42). Furthermore, autistic traits in the children have been associated with the severity of nausea and 'morning sickness' during pregnancy, symptoms that are also linked to high hCG levels (43,44).…”
Section: Association Of Hormones With Infant Q-chat Scorementioning
confidence: 99%